Young coffee (Ingeniería, Sostenibilidad y Sociedad, 2023)
This work evaluates the different meanings and motives that lead young people between 20 and 30 years old to consume Colombian coffee. The cultural differences that can arise with respect to consumer behavior are evident, in addition to the different reasons that drive him to behave.  Miau Desserts is a new cafeteria and biscuit concept at the University of Pamplona headquarters Villa del Rosario, where the main attraction is coffee with different flavors and good product quality, and accompaniment of biscuit and pastry type. This project tries to make a pleasant communication and release of stress for the student and the teacher, through good flavors and establishing the brand of artisan cookies Miau Desserts.
Keywords: Culture; motivation; values; youth; university